Surface DEAE groups facilitate protein transport on polymer chains in DEAE‐modified‐and‐DEAE‐dextran‐grafted resins. Issue 10 (26th July 2016) - Yu, Linling; Gong, Lingli; Bai, Shu; Sun, Yan
Abstract : Sepharose FF was modified with diethylaminoethyl‐dextran (DEAE‐dextran, DexD) and/or DEAE (D) to fabricate three types of ion exchangers FF‐DexD (grafting‐ligand resin), FF‐D (surface‐ligand resin), and FF‐D‐DexD (mixed‐ligand resin), for protein adsorption equilibria and kinetics study. It was found that both adsorption capacity and uptake rate (effective diffusivity, De ) were significantly enhanced by grafting DEAE‐dextran. Notably, the De values on FF‐DexD and FF‐D‐DexD (De /D0  > 1.4) were six times greater than those on FF‐D (De /D0  < 0.3). More importantly, the increase of surface‐ligand density greatly enhanced uptake kinetics on FF‐D‐DexD. The results indicate that the surface ligands assisted the transport of bound proteins on polymer chains in the mixed‐ligand resins. That is, surface ligands worked as "transfer stations" between two neighboring chains, resulting in enhanced transport of bound proteins on chains. The research thus disclosed the unique role of surface ligands in facilitating protein uptake kinetics onto polymer‐grafted ion‐exchangers. © 2016 American Institute of Chemical Engineers AIChE J, 62: 3812–3819, 2016